Preparation of composite‐imprinted alumina membrane for effective separation of p‐hydroxybenzonic acid from its isomer using Box–Behnken design–based statistical modeling. Issue 16 (13th March 2014) - Meng, Minjia; Feng, Yonghai; Liu, Yan; Wang, Yun; Yan, Yongsheng
ABSTRACT Highly selective composite imprinted membrane for p‐hydroxybenzonic acid (p‐HB) was prepared by using semicovalent imprinting technique. A thermally reversible covalent bond was used to link p‐HB molecule to a functional alkoxysilane monomer to generate covalently bound imprint precursor. This precursor was incorporated into a cross‐linked functional silica sol with the tetraethoxysilane as cross‐linker via a typical acid‐catalyzed, sol‐gel synthesis. Then, the SCIM was prepared through dipping and grafting on the upper side and inner pores of the Al2O3 microporous membrane and then removing of the template molecule after thermal treatment. Compared with composite imprinted membrane via noncovalent imprinting approach as well as the black Al2O3 microporous membrane, the SCIM exhibited higher membrane flux and selective rebinding of p‐HB as well as showing excellent permeability for p‐HB. Response surface methodology was used to investigate the best combination of separation conditions in the dynamic separation process. The optimal conditions for the separation of p‐HB from salicylic acid were as follows: the p‐HB concentration of 5 mg L−1, the temperature of 10°C, and the flow rate of 1 mL min−1. Under these conditions, the experimental selective separation factor was 32.75 ± 0.91%, which was close to the predicted selectivity coefficient value. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40621.